The Ability of Mathematical Representation of Junior High School Students on Circle Material Based on Gender Differences - Soviana, Rena; Sutiarso, Sugeng; ., Nurhanurawati (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
Mathematical representation is the ability to express ideas or definitions raised by the students when solving problems. At now, most students have difficulties in the ability of mathematical representation. The difficulty of this mathematical representation needs to be analyze the causes, including analysis based on gender differences. This type of research is a qualitative study which aims to systematically describe the ability of mathematical representation based on gender differences. The subjects of the study was grade IX students at SMP Negeri 4 in Natar, South Lampung. Research subjects numbered 31 people, consisti of 16 boys and 15 girls. Data was collected through tests and observations, and data were analyze descriptively based on 3 indicator levels, namely visual representations, mathematical expressions or similarty, and written words or texts. The results showed that there were differences in representation when viewed regarding gender, where girls make more representation than boys.